The impact of CEO/CFO outside directorships on auditor selection and audit quality - YU, Jaeyoon (Institutional Knowledge at Singapore Management University, 2021)
We examine whether outside directorships of chief executive officer/chief financial officer (CEO/CFO) and resulting network ties to auditors affect auditor selection decisions and subsequent audit quality. The network ties arise when the CEO/CFO of a firm (home firm) serves as an outside director of another firm that hires an auditor (connected auditor). Using a sample of firms that switch auditors in the post-Sarbanes-Oxley Act period, we find that home firms are more likely to appoint connected auditors. We also find that home firms hiring connected auditors experience a significant decline in subsequent audit quality, compared to those hiring non-connected auditors. Specifically, the increases in the likelihood of misstatements, the magnitude of absolute discretionary accruals, and the propensity to meet or beat earnings benchmarks after home firms appoint connected auditors are significantly greater, compared to those for other firms switching to non-connected auditors. We further find that the decline in audit quality is more pronounced when the network is established at the local office level.